Genómica comparativa de cuatro cepas de Xanthomonas phaseoli pv. manihotis con capacidad metabólica y patogenicidad contrastante (2021)
Xanthomonas phaseoli pv. manihotis (Xpm) is the causal agent of cassava bacterial blight (Manihot esculenta), one of the most relevant biotic diseases that affects tropical crops due to the economic losses it generates. Recently, the hydrolytic activity of 660 Xpm strains were experimentally characterized, from which the most contrasting ones in xylanolytic and cellulolytic enzymatic activity were chosen. Furthermore, two very closely contrasting strains in the ability to cause disease were chosen to study the source of pathogenicity. The chosen strains were sequenced, assembled, and compared by different methods, in search of genetic variation related to xylanolytic enzymatic activity and pathogenicity. A GO enrichment analysis was performed from missense variants in the comparison for xylanolytic capacity and compile a list of genes affected by variations, which will be useful for further analysis and experimental validations.